(untitled) (The Human Voyage, 2018)
Simulations and animal studies provide a model where paratisim risk is associated with less modular social group sizes. Therefore, this study will examine whether the adoption of modular living in humans has been an adaptive strategy to minimise pathogen stress. Subsequently, codes for pathogens stress are analysed for their correlation with variables for household form, as described for 186 socieites in the Standard Cross-Cultural Sample. The resulting analysis found that pathogen stress is significantly higher for societies which adopt more communal living styles, but there is no differenece in mobile or contagious pathogens which would be expected for the mechanism of such a difference. More studies are still needed to rule out possible confoudning factors.